CAR-T Therapy Beyond B-Cell Hematological Malignancies - Martina Canichella; Paolo de Fabritiis (Cells)
Despite the advances of CAR-T cells in certain hematological malignancies, mostly from B-cell derivations such as non-Hodgkin lymphomas, acute lymphoblastic leukemia and multiple myeloma, a significant portion of other hematological and non-hematological pathologies can benefit from this innovative treatment, as the results of clinical studies are demonstrating. The clinical application of CAR-T in the setting of acute T-lymphoid leukemia, acute myeloid leukemia, solid tumors, autoimmune diseases and infections has encountered limitations that are different from those of hematological B-cell diseases. To overcome these restrictions, strategies based on different molecular engineering platforms have been devised and will be illustrated below. The aim of this manuscript is to provide an overview of the CAR-T application in pathologies other than those currently treated, highlighting both the limits and results obtained with these settings.